PENGARUH WORD OF MOUTH, HARGA, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN MOTOR LISTRIK DI KABUPATEN PONOROGO - Firdaus, Ferry Brian Nicholas; Rafida, Veni (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2024)
As progress in the automotive sector progresses, motorbikes are starting to switch to using electric motors. When buying an electric motorbike, potential consumers will consider the influence of word of mouth, price and product quality. The aim of this research is to analyze the influence of word of mouth, price and product quality on purchasing decisions for electric motorbikes in Ponorogo Regency. Primary data was obtained through a Google Form questionnaire filled in by 105 respondents. Data analysis was carried out using a quantitative descriptif approach using multiple linear regression with the SPSS 25 application. The results of this research show that word of mouth and product quality influence purchasing decisions, while price has no influence on purchasing decisions for electric motorbikes in Ponorogo Regency. It is hoped that the implications of this research will provide a deeper understanding of the factors that influence the decision to purchase electric motorbikes in Ponorogo Regency, as well as provide recommendations for manufacturers or related industry players to improve their marketing strategies in facing the increasingly growing electric motorbike market.